The Potent Audience and Changes in Journalism: A Look at the Spanish lavanguardia.com and the Latin American diariodepernambuco.com - Mesquita, Giovana Borges (Brazilian journalism research, 2016)
The possible transformations in the way journalistic contents are being produced, consumed and distributed is the motivation for our graduate degree research. This article has the following objectives: to present our description of a potent audience; to analyze how it has been involved in and what changes it has brought forth in the news production for two reference vehicles, after what has been called WEB 2.0. It also has the relevance of relying on the findings of the participant observation carried out in one of the most important daily newspapers in Barcelona, the lavanguardia.com, and in the diariodepernambuco.com, the online version of the Diario de Pernambuco, the oldest newspaper still in circulation in Latin America. Both newspapers are pioneers in this new reference vehicle-potent audience relationship.